Transcriptional distinctions between normal and glioma-derived A2B5(+) progenitor cells identify a core set of genes dysregulated at all stages of gliomagenesis - Auvergne, Romane M. (Cell Rep, 2013)
Glial progenitor cells (GPCs) are a potential source of malignant gliomas. We used A2B5-based sorting to extract tumorigenic GPCs from human gliomas spanning WHO grades II-IV. mRNA profiling identified a cohort of genes that distinguished tumor-initiating progenitor cells (TPCs) from A2B5(+) GPCs isolated from normal white matter. A core set of genes and pathways was substantially dysregulated in A2B5(+) TPCs, that included the transcription factor SIX1, and its principal co-factors, EYA1 and DACH2. shRNAi silencing of SIX1 inhibited the expansion of glioma TPCs in vitro and in vivo, suggesting a critical and unrecognized role of the SIX1-EYA1-DACH2 system in glioma genesis or progression. By comparing the expression patterns of glioma TPCs to normal GPCs, we have identified a discrete set of pathways by which glial tumorigenesis may be better understood, and more specifically targeted.